Towards an effective participatory process for a sustainable urban waterfront development - Yusri Syahrir (Communications in Humanities and Social Sciences, 2021)
During the early time of waterfront development, public only paid little attention to this area, but after a series of urban waterfront revitalization success story, people are starting to reclaim their waterfront. Two main values of economy and environment are always competing over waterfront’s future land-use pattern. Citizen participation in an urban waterfront development is believed to hold a significant importance since the urban development is addressed for citizens’ prosperity. However, strong public participation does not necessarily guarantee for a success waterfront development. This paper attempts to figure out what is the best scenario to make public involvement in the planning process to contribute to a successful and sustainable waterfront development. Four waterfront city development stories that represent different planning cultures were examined here to understand to what extent the participatory process contributed to the environment, economy, and social values. The findings from the case studies were reconstructed to develop a planning model aimed to best accommodate public interest without compromising other values. Citizens were invited for discussions at the initial phase. Next, an evaluation method was proposed to come up with a guideline that would guide the planning process at the latter phase.